"They absolutely don’t want you to progress here" - Samuli Skurnik; Mikael Skurnik (Nordisk Judaistik)
Fascism and Nazi ideology cast a threatening shadow over Finland during its troubled 1930s. This manifested as antisemitism towards the few Jewish students pursuing higher degrees at Finnish universities. One glaring instance of discrimination involved our father, Leo Skurnik, whose advancement in his academic career was blocked at the Helsinki University Department of Medical Chemistry in the late 1930s. In this treatise, we aim to delve deeper into the challenges he faced and how they were intertwined with the antisemitic sentiments prevailing at that time.